2016
DOI: 10.15586/jkcvhl.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Lysosomal Sequestration in Sunitinib Resistance of Renal Cell Cancer

Abstract: Renal cell carcinoma (RCC) is a highly vascularized tumor type, which is often associated with inactivated mutations in the von Hippel-Lindau gene that drives proangiogenic signaling pathways. As such, new therapies for the treatment of RCC have largely been focused on blocking angiogenesis. Sunitinib, an antiangiogenic tyrosine kinase inhibitor, is the most frequently used first-line drug for the treatment of RCC. Although treatment with sunitinib improves patient outcome considerably, acquired resistance wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…Additionally, nuclear translocation of TFEB was observed after MEK inhibition and a corresponding upregulation of its target genes. This may point to the fact that MEK inhibition in PDAC induce lysosomal biogenesis and foster lysosomal drug accumulation and subsequent exocytosis as previously hypothesized 32 . To verify this hypothesis, we isolated lysosomes from trametinib-treated cells and using mass spectrometry,we were able to detect the presence of trametinib in these organelle.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Additionally, nuclear translocation of TFEB was observed after MEK inhibition and a corresponding upregulation of its target genes. This may point to the fact that MEK inhibition in PDAC induce lysosomal biogenesis and foster lysosomal drug accumulation and subsequent exocytosis as previously hypothesized 32 . To verify this hypothesis, we isolated lysosomes from trametinib-treated cells and using mass spectrometry,we were able to detect the presence of trametinib in these organelle.…”
Section: Discussionmentioning
confidence: 55%
“…Malignant cancer cells may adopt such mechanisms to guard against therapeutic assaults. Indeed, lysosomal drug sequestration has been reported for other anticancer agents 36 and is responsible, at least in part for drug resistance 32,37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…This effect was however found to be additive at the highest concentration tested, indicating that the mechanism of sunitinib resistance is not related to lysosomal sequestration. Lysosomal sequestering of sunitinib has been associated with resistance by others [7,29,31]. To our knowledge, direct experiments addressing the cytotoxic impact of lysosomal accumulation of sunitinib in resistant cells has only been included in two reports where only modest increase in sunitinib toxicity was reported by combining sunitinib with Leu-Leu-O-Methyl in vitro [29] or chloroquine in vivo in sunitinib-resistant HT-29 xenografts [30].…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal accumulation of sunitinib has been reported as a mechanism of resistance [7,[28][29][30][31][32] and we tested if PCI could counteract this mechanism by releasing endosomal sunitinib sequestered during long-term exposure. Sunitinib resistant HT-29 cells, HT-29/SR, was generated by continuous exposure to 2 µM.…”
Section: Acquired Resistance and Endo/lysosomal Accumulation Followinmentioning
confidence: 99%
“…For sunitinib, the lysosomal accumulation has also been demonstrated by using its fluorescent properties which co-localized with the Lysotracker, a marker for lysosomes [7]. Moreover, pre-incubation with Bafilomycin-A prevented trapping of sunitinib in the lysosomes [7,16]. Sunitinib achieves very high cellular concentrations since it has been shown that 90% of accumulated drug is held within lysosomes within the cell structure.…”
Section: Discussionmentioning
confidence: 99%